2006
DOI: 10.1210/jc.2006-0584
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Triglyceride Content and Epicardial Fat Mass in Human Obesity: Relationship to Left Ventricular Function and Serum Free Fatty Acid Levels

Abstract: The accumulation of triglyceride in and around the myocardium of moderately obese individuals is significant, and it is related to FFA exposure, generalized ectopic fat excess, and peripheral vascular resistance. These changes precede LV overload and hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
223
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 303 publications
(249 citation statements)
references
References 30 publications
15
223
2
3
Order By: Relevance
“…Previous studies have suggested an association between pericardial fat and cardiac function. 31,32 Kankaanpaa et al 32 showed in a very limited population (n ¼ 9) that EF was inversely correlated with CI. By contrast, Iozzo et al showed that MTGC was independently and positively associated with cardiac output, LV forward work, cardiac work and CI, but not with pericardial fat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested an association between pericardial fat and cardiac function. 31,32 Kankaanpaa et al 32 showed in a very limited population (n ¼ 9) that EF was inversely correlated with CI. By contrast, Iozzo et al showed that MTGC was independently and positively associated with cardiac output, LV forward work, cardiac work and CI, but not with pericardial fat.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] MRI was recently used in mildly obese patients to suggest that the increase in MTGC could be associated with cardiac dysfunction. [31][32][33] To date, no study has addressed the relationship between EFV and MTGC in morbidly obese patients, a population with an abundance of fat in different depots and a high risk of cardiac failure, 34 because of the relatively small diameter of the MRI magnet bore. In this study, we had the opportunity to quantify EFV and MTGC in a cohort of severely obese subjects using a 70-cm bore, 3-T MRI system.…”
Section: Introductionmentioning
confidence: 99%
“…Although a limit-based error analysis of the relaxation correction has been published [37], many studies report CV's based only on repeated acquisitions and do not include the uncertainty of the T 2 correction [5,8,9,12]. For species with comparatively long T 2 's, such as brain metabolites, the additional uncertainty is minor.…”
Section: Relaxationmentioning
confidence: 99%
“…Localized magnetic resonance spectroscopy (LMRS), which uses gradient-enabled imaging systems, is increasingly used both in basic and clinical assays including qualitative and quantitative compositional, temperature, and pH measurements [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Kreiss [16] summarized the main aspects of LMRS, including spectral artifacts, systematic errors, and general criteria for ensuring spectral quality.…”
Section: Introductionmentioning
confidence: 99%
“…A progressive increase in myocardial fat content has been observed in obese and type 2 diabetic patients [1], and has been shown to correlate with a decline in left ventricular function and signs of cardiomyopathy [2,3]. Increased myocardial triacylglycerol (TG) storage may reflect an imbalance between the supply and utilisation of fatty acids.…”
Section: Introductionmentioning
confidence: 99%